STUDI LITERATUR EFEKTIVITAS PEMBERIAN TANAMAN OBAT DALAM PENYEMBUHAN LUKA PERINEUM PADA IBU NIFAS - Fauziah, Fuzi (Jurnal Komunitas Farmasi Nasional, 2024)
Aim: This study aims to determine which medicinal plants and plant parts are most effective in healing perineal wounds in postpartum women and to find out information regarding the secondary metabolite content in plants which have activity in treating perineal wounds. Method: This research uses a literature study method by conducting journal searches using the Harzing's Publish or Perish application which is connected to database sources such as Google Scholar, PubMed, and Science Direct. Journal searches used the keywords "luka perineum", "tanaman obat", "perineal wound", and "medicinal plants". Journal selection was carried out based on inclusion and exclusion criteria. Results: The results of the study showed that there were 13 journals that met the inclusion criteria, and it was found that 12 plants were effective in healing perineal wounds including silymarin, aloe vera, rosemary, torbangun, red betel, green betel, st. John's wort, sidaguri, black cumin, turmeric, common mullein and green tea. Conclusion: The most effective plant in healing perineal wounds is the Silymarin plant (Silybum marianum). The most widely used part of the plant is the leaves. Secondary metabolite compounds contained in almost all plants are flavonoids.